2021
DOI: 10.1111/jgs.17622
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with resident‐to‐resident elder mistreatment in nursing homes

Abstract: Background: Resident-to-resident elder mistreatment (RREM) in nursing homes has serious physical and psychological consequences, but factors related to RREM occurrence remain unclear. This study identifies individual and environmental characteristics associated with involvement in RREM episodes. Methods:The design was an observational study carried out in five urban and five suburban New York state nursing homes randomly selected on the basis of size and location. The sample consisted of 2011 residents in 10 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Other research has also found higher prevalence estimates of RRA among residents in memory care units. An earlier retrospective case record study has shown that the incidence of aggressive behavior per resident per year was almost 3 times as likely among residents in memory care units than among residents in the rest of the facility . A major reason for this higher prevalence is that individuals with dementia and behavior problems resulting from it are congregated closely.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Other research has also found higher prevalence estimates of RRA among residents in memory care units. An earlier retrospective case record study has shown that the incidence of aggressive behavior per resident per year was almost 3 times as likely among residents in memory care units than among residents in the rest of the facility . A major reason for this higher prevalence is that individuals with dementia and behavior problems resulting from it are congregated closely.…”
Section: Discussionsupporting
confidence: 85%
“…This finding aligns with findings from a prior nursing home study using a nearly identical methodological approach, with rates of 29.0% in dementia care units vs 18.5% in nondementia care units . Potentially associated with this finding is that a larger proportion of residents (39.7%) resided in memory care units in our assisted living facility sample as contrasted with 16.3% in the nursing home sample …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, DSCUs were associated with better resident outcomes and quality of care (e.g., decreased use of feeding tubes, antipsychotic medications, and physical restraints; fewer hospitalizations and pressure ulcers) 82–85 . Other studies reported less favorable outcomes among residents in DSCUs, including lower levels of social connectedness 86 and higher risk for elder‐to‐elder mistreatment, 87 deficiency citations, 88 infections, 89 and antipsychotic use 90,91 …”
Section: Resultsmentioning
confidence: 99%
“…In some cases, DSCUs were associated with better resident outcomes and quality of care (e.g., decreased use of feeding tubes, antipsychotic medications, and physical restraints; fewer hospitalizations and pressure ulcers). [82][83][84][85] Other studies reported less favorable outcomes among residents in DSCUs, including lower levels of social connectedness 86 and higher risk for elder-to-elder mistreatment, 87 deficiency citations, 88 infections, 89 and antipsychotic use. 90,91 Results from a pilot study using combinations of social network analysis methods demonstrated that staff-to-resident interactions T A B L E 3 Summary of reviewed descriptive study articles in the United States (N = 13).…”
Section: United Statesmentioning
confidence: 99%